Comparison of Sum of Two Correlated Gamma Variables for Alouini's Model and McKay Distribution - Roslinazairimah, Zakaria; J. W., Boland; Nor Hafizah, Moslim (2013)
A statistical model for rainfall is useful to describe the relationship between rainfall at a given location and other weather-related variables. It is also able to provide a principled way to quantify the uncertainty that associates rainfall processes, which is crucial to the efficient design of environmental projects and to improve crop production. Various statistical models have been used for rainfall such as a right-skewed distribution including the exponential, gamma or mixed-exponential to model the rainfall intensities and Markov chain model to model rainfall occurrences.